Adaptive finite-time output-feedback control design for switched pure-feedback nonlinear systems with average dwell time. (August 2020) - Ma, Li; Xu, Ning; Huo, Xin; Zhao, Xudong
Abstract: In this paper, the issue of adaptive fuzzy tracking control is addressed for a class of completely non-affine uncertain switched pure-feedback nonlinear systems with unmeasurable states. In such a system, the average dwell time switching rule is adopted, and its stability is discussed for the first time in the sense of finite time. A fuzzy logic system-based switched observer is constructed to approximate unmeasurable states, which reduces the conservativeness stemming from utilizing a common observer for all subsystems. In addition, filter signals are applied to avoid algebraic loop problem existing in adoption of the controller. Then, a novel adaptive finite-time control strategy is developed on the basis of multiple Lyapunov functions approach, dynamic surface control and backstepping technique. It is proved that the designed controllers of subsystems can ensure that all the closed-loop signals are bounded under a class of switching signals with average dwell time, while the tracking error can converge to a small area of the origin in a finite time. Finally, two simulation examples are given to demonstrate the validity of the proposed control scheme.